2018
DOI: 10.1016/j.algal.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale production of poly-β-hydroxybutyrate with the cyanobacterium Synechocytis sp. CCALA192 in a non-sterile tubular photobioreactor

Abstract: Poly-β-hydroxybutyrate (PHB) is considered as one of the most promising bioplastics. It has a broad range of applications and is degraded relatively rapidly by soil organisms. Like many prokaryotes, the cyanobacterium Synechocystis sp. CCALA192 produces this biopolymer as a storage compound, especially under nutrient starvation.In a 200-liter tubular photobioreactor, we cultivated Synechocystis sp. CCALA192 semi-continuously over a period of 75 days with CO 2 as sole carbon source. A two-stage cultivation stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 51 publications
(55 reference statements)
5
25
0
Order By: Relevance
“…PCC 6714 BG11 Jacketed glass photobioreactor (1 L), under nitrogen and phosphorus limitation for 15 days 16.4 ± 2.0 [ 25 ] Synechocystis sp. CCALA192 BG11 Tubular photobioreactor (200 L), under complete BG11 medium cultivation for 20 days 12.7 [ 26 ] Synechocystis sp. PCC 6803 strain ∆SphU BG11 Flat-plate photobioreactor (10 L), under complete BG11 medium cultivation for 13 days (control condition) 6.42 ± 1.8 This study Synechocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…PCC 6714 BG11 Jacketed glass photobioreactor (1 L), under nitrogen and phosphorus limitation for 15 days 16.4 ± 2.0 [ 25 ] Synechocystis sp. CCALA192 BG11 Tubular photobioreactor (200 L), under complete BG11 medium cultivation for 20 days 12.7 [ 26 ] Synechocystis sp. PCC 6803 strain ∆SphU BG11 Flat-plate photobioreactor (10 L), under complete BG11 medium cultivation for 13 days (control condition) 6.42 ± 1.8 This study Synechocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Troschl et al could report 12.5% PHB cry well weight [21]. In the same year, Kamravamanesh et al have shown that the cyanobacterium Synechocystis sp.…”
Section: Phb Production By Cyanobacteria: Current State Of Knowledgementioning
confidence: 99%
“…It is known that cyanobacteria can produce PHB as an intracellular energy and carbon storage compound [21] (see Figure 1).…”
Section: Phb Production By Cyanobacteria: Current State Of Knowledgementioning
confidence: 99%
“…The maximum PHB content of 125 mg L −1 was obtained for the non-sterile batch cultivation of Synechocystis sp. CCALA192 in a 200-L tubular photobioreactor [42]. Moreover, PHB was produced using optimized media in a one-liter tank reactor for the wild-type cyanobacterial strain Synechocystis sp.…”
Section: Production Strategiesmentioning
confidence: 99%